The novel antimicrobial Prosopis juliflora leaf ethanolic extract and its effectiveness in extending cucumbers postharvest shelf-life - Iman Saleh (14152878) (2023)
Cucumber (Cucumis sativus) is an economically important vegetable worldwide with a short shelf life. The agricultural domain is one of the booming sectors in Qatar, the country provides now a high percentage of its local needs in cucumber. Due to the unfavorable climate conditions, crops production in the country is costly. In addition, Qatar population has increased by 92.8% between 2008 and 2020, this has led to an increase by 225.8% in the cost of imported fruits as per the planning and statistics authority, Qatar. Cucumber import alone has costed the country 22.5MM QR in 2020, therefore, any losses in this fresh produce during storage will cost the country millions. Prosopis juliflora is an invasive plant in Qatar. Prosopis juliflora water‐soluble leaf ethanolic (PJ‐WS‐LE) extract has a strong antimicrobial activity against many spoiling agents with time‐stability and no phytotoxicity on fruits. The present study explores PJ‐WS‐LE extract efficacy as a coating material to preserve cucumber. 8 mg/ml of PJ‐WS‐LE extract increased cucumber shelf life at 22°C by 77%. In vivo overall results highlight the potentials of PJ‐WS‐LE extract as a possible coating replacement of chemical fungicides. Results support the protection of locally produced vegetables and provide sustainability to the environment by controlling P. juliflora invasion by utilization and by protecting the environment from the side effects of pesticides.